AB0457 Patient Reported Adverse Events on Rituximab Treatment for Rheumatoid Arthritis. (9th June 2015) - Visman, I.M.; Agca, R.; Voskuijl, A.; Nurmohamed, M.
Abstract : Background: After the success of TNF blocking therapy, a number of new biological therapies have emerged for patients with rheumatoid arthritis (RA). Rituximab is a B cell blocking agent and a good alternative to TNF blocking therapy. One issue that arises with any therapy, but biological therapy in particular, is adverse events. Reporting on serious adverse events (SAE) is mandatory. However, most adverse events patients experience are mild or moderate, and do not come close to the seriousness of an SAE. Nevertheless, these patient reported adverse events (PRAE) directly affect patient satisfaction with treatment, and are an important reason to discontinue treatment. Objectives: To ascertain the number and severity of PRAE of long- term rituximab treatment for RA Methods: The first rituximab patient was included February 9th 2009 and up to February 20th 2014 a total of 97 patients have been included at the Jan van Breemen research centre in Amsterdam, the Netherlands. Results: The median follow-up duration was 1.1 (IQR:0.6-1.9) years for patients currently still on rituximab treatment, and 0.6 (0.1-1.1) years for drop-outs. The maximum follow-up duration was 3.8 years. Of the 97 patients included a total of 66 (68%) are currently on drug, and 31 (32%) patients have dropped out. Lack of efficacy was the most common cause for drop-out, with 14 (45%) patients. In addition, 11 patients (35%) discontinued rituximab treatment due to adverse events. An additional 2 patients (6%) never started rituximab treatment after inclusion, and for 2 patients (6%) the reason for drop-out was not given and 2 patients (6%) died during treatment. A total of 203 PRAE were observed in a total of 68 (70%) of patients. Reaction at site of injection was the most common adverse event observed during the follow-up (table 1 ). In 1 case a patient was hospitalized due to leukopenic fever (viral in nature), and 4 times antibiotics were given. Two patients died during rituximab treatment, one of a brain tumor, for the other cause of death was unknown. Conclusions: The vast majority of PRAE were mild (90%). Only one (25%) of the 4 severe AE fulfilled the criteria for an SAE report. In contrast, 11 patients (in consultation with their rheumatologist) found their subjective PRAE serious enough to permanently stop taking rituximab. Obviously, reporting SAEs only does not give an adequate representation of the adverse events patients suffer. The reporting of patient (dis)satisfaction measures such as PRAE is a valuable addition to the reporting of SAE's in studies, and to the decision making processes of rheumatologists. Disclosure of Interest: None declared